Connection Level Knowledge About Effect Side Treatment Chemotherapy With Support Family On Patient Cancer Colon - Herning Danastri; Andi Surya Kurniawan; Regista Trigantara (PROFESSIONAL HEALTH JOURNAL, 2024)
Background: Family knowledge of chemotherapy side effects has a relationship with family support in cancer patients. When the family has a good level of knowledge about the side effects of cancer treatment by chemotherapy, the family will increasingly provide support to family members who are cancer patients so that they can regularly, proportionately, and according to recommendations following chemotherapy treatment to achieve the healing process .Objective: This study aims to determine the relationship between the level of knowledge about the side effects of chemotherapy treatment with support in colon cancer patients .Methods: This research is a quantitative research research with a correlative type of analytics. Samples of family members of patients in the Semeru Room of Dr. Saiful Anwar Hospital Malang totaled 93 people. The research instrument used was a questionnaire .Results: The results showed that most respondents had good knowledge (49.5%). Most respondents were very supportive (66.7%) .Conclusion: The Spearman Correlation statistical test produces a correlation value of (0.249) where the correlation value shows a weak but positive relationship and a significance value of (0.016) where the significance value is < 0.05. The results of statistical tests showed a weak but positive and significant relationship between the level of knowledge about the side effects of chemotherapy treatment and support in colon cancer patients in the Semeru room of Dr. Saiful Anwar Hospital Malang. It is expected that the patient's family needs to listen carefully to this explanation in order to understand and provide appropriate support.